Rumours, myths, and misperceptions as barriers to contraceptive use among adolescent girls and young women in South Africa - Jonas, Kim; Duby, Zoe; Maruping, Kealeboga; Harries, Jane; Mathews, Catherine (Frontiers in Reproductive Health, 2022)
Background Rumours, myths, and misperceptions about contraceptives are a barrier to contraceptive use in general, but more so among adolescent girls and young women (AGYW). As rumours and misinformation disseminate easily, it is important to explore how they affect the uptake of contraceptives among AGYW at risk of unintended pregnancies. This study used qualitative methods to explore whether rumours, myths, and misperceptions about contraceptives remain barriers to modern contraceptive use among AGYW who were beneficiaries of a combination HIV prevention intervention in South Africa. Methods Four (4) once-off in-depth interviews, 53 serial in-depth interviews, and 19 focus group discussions (FGDs) with 185 AGYW aged 15–24 years living in 5 of the 10 intervention districts were conducted as part of the HERStory 1 Study. Interviews and FGDs were audio recorded and data were analysed thematically, aided by Nvivo 12 software. Results Rumours, myths, and misperceptions about contraceptives, as well as sociocultural norms regarding contraception seriously hinder AGYWs’ use of modern contraceptives. Peer/friends’ disapproval and parents’ and boyfriend’s lack of support for AGYWs’ use of contraceptives, based on rumours and perceived side effects, also impede AGYWs’ access and use of contraceptives. Conclusion Sexual and reproductive health programmes could address social norms that disapprove of contraception and target rumours, myths, and misperceptions regarding modern contraceptive methods through educational campaigns and community engagements. Promoting the use of contraception in the community and men’s acceptance of contraceptive use, in particular, may increase their understanding of modern contraceptives and, subsequently, their approval for their partners to use them.